Conflict Management in Indonesia: Policy Perspective and Analysis - Arjon, Sugit S. (RMPI-BRIN, 2018)
This article focuses on analysing the roots of violence and examines case studies in Indonesia. This article aims at determining the effectiveness of policies in conflict management by analysing the critical factors involved in violent conflicts and briefly seeking alternative solutions to prevent them from happening in the future. Furthermore, this article aims to answer two central questions. Firstly, this study looks at how effective the Indonesian government’s policy on security and conflict is. Secondly, this study considers the roles of NGOs in supporting the effectiveness of the policy on security and conflict. To prevent future conflicts, there are three effective strategies that can be implemented, and they require collaboration between policymakers and society. The first strategy involves designing an effective early warning mechanism, which would be able to inform the government of a potential friction that could escalate to a larger conflict. The second strategy is an effective policy to prevent and manage conflict and provide peace building mechanisms post-conflict. The third strategy is to urge the participation of non-state actors in conflict management. The Indonesian government and House of Representatives (Dewan Perwakilan Rakyat – DPR) have passed a bill on social conflict management written as Law No. 7/2012 and known as UU PKS. However, UU PKS arguably leaves numerous loopholes. Moreover, the activities of NGOs in conflict management can be divided into two main categories: public engagement and advocacy. Public engagement activities focus on services for the public, while advocacy focuses on maintaining communication and putting pressure on the government. In public engagement activities, NGOs offer services to provide psychological and legal assistance, consulting with victims on their rights as well as providing legal advice and psychosocial support to victims. Moreover, in the advocacy approach, NGOs maintain to put pressure and lobby the government to ensure peace and justice in law enforcement.